Evaluation of Implants, Clover, and Fescue Variety on Stocker Steers - Z. T. Buessing; J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2021)
Sixty-four growing steers were used in a split-plot experiment, where the whole plot was pasture, and the split-plot was implants. Whole plot treatment was a 4 × 2 factorial with four levels of fescue (High Endophyte, Low Endophyte, Novel, or Endophyte Free) and two levels of legume (Legumes or No Legumes). The split-plot included four implant levels (No Implant, Synovex One Grass, Revalor-G, Ralgro). Data collected were weights, hair coat scores, hair length, rectal temperature (every 28 days), and ultrasound carcass characteristics coming off grass. Steers on High Endophyte had the lowest average daily gain (ADG), longest hair, and highest temperature as compared to steers on all other fescue types. The gain differentiation was observed beginning at day 56 through the end of the study. Overall, ADG was not impacted by the addition of legume nor implant type. Steers that were not implanted had a longer hair length throughout many measurement dates. Steers grazing pastures with legumes tended to have a higher ultrasound-measured marbling score and less muscle depth. This study found that the best management strategy for fescue toxicity is to use non-endophyte or non-toxic varieties of fescue pasture. Contrary to previous research, the addition of implants and legumes for this project showed no improvement in cattle gains.
Keywords: fescue; clover; implant; cattle gain; hair score; fescue toxicity; pasture; grazing